Humanist Proselytizing in Disruptive Era - Syam, Nur (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2022)
The disruptive era is happening not only in social and political life but also in religious life. Based on this reality, this study aims to describe humanist proselytizing in disruptive era, whit philosophical perspective of Humanism. The result of this study indicates, that Islam is a religion that prioritizes human dignity as the essence of life. Islam teaches that it should be spread with a humanistic approach that prioritizes the glory of humans as God's creation. Humanist proselytizing presupposes that proselytizing is held to improve religious understanding and action to be in harmony with the Islamic teachings glory. Humanist proselytizing, through populism of religious moderation and strengthening of religious moderation preachers is needed to build a better, prosperous, and happy society. This strategy is chosen amidst the challenges of strengthening lateral religious understanding in the disruptive era. This study argues, through the populism movement of religious moderation and the strengthening of religious moderation preachers, it is hoped that it will be able to strengthen moderate Islam as the message essence of humanist proselytizing.